Grazing cattle on winter cereal pasture on the sandy soils of south-central Kansas - Martin, Victor L.; Hale, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Rye, wheat, and triticale pasture were evaluated during the winters of 2000-01, 2001-02, and 2002-03 for their ability to increase cattle weight from late fall through mid-spring. Large-scale studies were conducted on two 80-acre sites divided into either 25- or 40-acre pastures. Cattle at these sites were stocked at one head per acre, with an average initial weight between 500 and 550 lb. At the Sandyland Experiment Field, small-scale studies were conducted by using the same winter cereals for forage, but at greater stocking rates, ranging from two to three head per acre. Supplemental feeding, as necessary, included summer annual forage hay, prairie hay, and grain consisting of wheat middlings and processed grain sorghum. Winter cereals were planted at 100 lb/acre in September of each year. Rye provided the best pasture in terms of cattle weight gain and needed the least supplemental feeding. Wheat was next in producing pounds of beef, and triticale produced less gain than either rye or wheat. These data suggest that rye and wheat were able to support greater stocking rates than triticale.
Keywords: Beef; Winter cereal pasture; South-central Kansas